Handbook of Genetic Diagnostic Technologies in Reproductive Medicine Improving Patient Success Rates and Infant Health - Simón, Carlos; Rubio, Carmen (Taylor & Francis, 2022)
Image-based and sequencing-based spatial technologies can currently be used to locate cells anatomically within a tissue; the Human Vell Atlas allows its users to navigate the human body at various levels of resolution to identify patterns and interactions among its fundamental elements, zooming in and out depending on the research goals. Integrating data types or simultaneously measuring multiple modalities is invaluable when defining cell identities.